Home energy efficiency under net zero: time to monitor UK indoor air - Petrou, Giorgos; Hutchinson, Emma; Mavrogianni, Anna; Milner, James; Macintyre, Helen; Phalkey, Revati; Hsu, Shih-Che; Symonds, Phil; Davies, Michael; Wilkinson, Paul (The BMJ, 2022)
Giorgos Petrou and colleagues argue for systematic large scale monitoring of indoor air to avoid unintended harms to health from home energy efficiency programmes
Gesehen am 27.06.2022